Geotechnical and Geophysical Methods for Water Content Prediction of Compacted Soil Southern Baqubah City - Hassan, Asem; Usama, Gehan (ASJ - Academic Science Journal, 2023)
Water content affects the soil state, consistency, and engineering behavior of various engineering projects. Evaluation of water content is, therefore, crucial to maintain the stability of these projects. Geotechnical and geoelectrical techniques are integrated in this study to characterize the soil, with a particular interest in the water (moisture) content, southern Baqubah City. Twenty soil specimens, manually collected using a hand Auger and the core cutter method, were used. Basic geotechnical tests were first implemented to characterize and classify the soil. Secondly, compaction characteristics referred to as, Optimum Moisture Content (OMC) and Maximum Dry Density (MDD), were determined using Standard Proctor compaction (SPC) and Modified Proctor Compaction (MPC) tests, which are essential to evaluate the compaction process. Thirdly, the resistivity of the compacted specimens was measured and compared with soil water content obtained using the oven drying method. ASTM standards were followed in all laboratory tests. Finally, geotechnical and geoelectrical methods were integrated for water content prediction. The results showed that, based on USCS, the soil is of low plasticity, fine-grained type (CL) and (CL-ML). The average LL, PL, and PI values were 25.50, 18.61, and 6.89, respectively. The average MDD and OMC values were 1.75 g/cm3, and 17.18%, for SPC tests, and 1.90 g/cm3 and 13.24%, for MPC tests, respectively. The resistivity was non-linearly correlated with water content with R2 values (>0.99) for all samples which indicates the potential of using this method, as a non-destructive and low-cost method, for the evaluation of the water content of compacted soils. The relationships between the measured and predicted values for SPC (R2=0.911) and MPC (R2=0.934) tests, respectively, confirm the usefulness of using the resistivity method to provide a quick and preliminary evaluation of soil water content.